IMPLEMENTASI KEBIJAKAN RUANG TERBUKA HIJAU PRIVAT DI KECAMATAN PEDURUNGAN KOTA SEMARANG - Dian Rahmadhani; Hartuti Purnaweni; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Increasing of using areas can causes the decreasing of green open space availability. Beside that, the decreasing of green open space also caused by judgment that the green open space is reserve area and not economical. To cover up the less area of green open space, can be done with increasing the people participations to increasing the private green open space. The purpose of this research is to find out about the policy implementation of private green open space in Pedurungan Subdistrict, Semarang City by “Five Appropriates” are Policy Accuracy, Implementation Accuracy, Target Accuracy, Environmental Accuracy and Process Accuracy. The second purpose is to find out the support and the inhibitor factors that involves in implementation process of private green open space in Pedurungan Subdistrict, Semarang City by observe in: Communication, Resources, and Authorizing Signature. The results conclude that implementation of private green open space in Pedurungan Subdistrict not optimal yet; it shows that there are people not known about implementation of private green open space yet. The inhibitor factors in implementation of private green open space in Pedurungan Subdistrict are communication that not optimal yet, and the resources that not equal yet, especially government human resource to do socialization that still definite. The support factors in policy implementation is about government commitments and responsibilities to increasing socialization about policy of private green open space in Pedurungan Subdistrict. Recommendations from the results research are: (1) To increase the private green open space directly, in order that people known about the policy; (2) Socialization can be done with interesting method; (3) increasing the human resources.